2022
DOI: 10.3389/fphys.2022.923185
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Demethylase AlkB Homolog H5 in the Promotion of Dentinogenesis

Abstract: Dentinogenesis is a key process in tooth formation and is regulated by a series of pre- and post-transcriptional regulations. N6-methyl-adenosine (m6A), which is the most prevalent internal chemical modification that can be removed by the RNA demethylase AlkB homolog H5 (ALKBH5), has recently been reported to be involved in several biological processes. However, the exact function of ALKBH5-mediated m6A modification in tooth development remains unclear. Here, we showed that Alkbh5 was expressed in pre-odontobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Methyltransferase-like 3 (METTL3) knockdown inhibits odontogenesis in dental roots by affecting nuclear factor I-C translation [41]. Conditional knockout of the demethylase alpha-ketoglutarate-dependent dioxygenase alkB homolog 5 (ALKBH5) in odontoblasts resulted in dysfunctional primary dentinogenesis [42]. Furthermore, FTO depletion resulting in dentine formation defects in mice has been reported [20].…”
Section: Discussionmentioning
confidence: 99%
“…Methyltransferase-like 3 (METTL3) knockdown inhibits odontogenesis in dental roots by affecting nuclear factor I-C translation [41]. Conditional knockout of the demethylase alpha-ketoglutarate-dependent dioxygenase alkB homolog 5 (ALKBH5) in odontoblasts resulted in dysfunctional primary dentinogenesis [42]. Furthermore, FTO depletion resulting in dentine formation defects in mice has been reported [20].…”
Section: Discussionmentioning
confidence: 99%
“…Pan et al [17] found that METTL3-enhanced dentinogenesis differentiation of dental pulp stem cells via increasing GDF6 and STC1 mRNA stability. Tian et al [18] found that Alkbh5 overexpression in the mouse dental papilla cell line mDPC6T promoted odontoblastic differentiation. In addition, a study demonstrated that m6A methylation is activated in PDLSCs after LPS treatment [19].…”
Section: Introductionmentioning
confidence: 99%